Miriam E. Cameron: Living with AIDS: Experiencing Ethical Problems - Jöhncke, Steffen (Tidsskriftet Antropologi, 1994)
Miriam E. Cameron: Living with AIDS: Experiencing Ethical Problems Anmeldes af Steffen Jöhncke